Determinants of crowd funders to use Crowdfunding-Waqf Model (cwm): A structural equation modeling approach - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin; Allah Pitchay, Anwar (2016)
This study is designed to examine the behavioural intention of crowd funders to use Crowdfunding-Waqf Model (CWM). The present study has proposed Crowdfunding-Waqf Model to assist Waqf institution in meeting their liquidity constraint in developing Waqf Waqf land in Malaysia. The primary data are collected from the survey administered to crowd funders in the Klang Valley (n=1000) and the analysis is conducted using Structural Equation Modeling (SEM). Furthermore, the model has validated its acceptance in the field by adopting the Technology Acceptance Model (TAM). This study has revealed that both the perceived usefulness and perceived easy to use are found to have a positive impact on the intention of crowd funders to used Crowdfunding-Waqf Model, which later assist Waqf institution to develop Waqf land in Malaysia. Furthermore, perceived easy to use has a positive relationship and direct effect with perceived usefulness micro entrepreneurs to use the Crowdfunding-Waqf Model.